Leveraging Patients' Social Networks to Overcome Tuberculosis Underdetection: A Field Experiment in India - Jessica Goldberg; Mario Macis; Pradeep Chintagunta (Institute of Labor Economics (IZA), 2018)
Peer referrals are a common strategy for addressing asymmetric information in contexts such as the labor market. They could be especially valuable for increasing testing and treatment of infectious diseases, where peers may have advantages over health workers in both identifying new patients and providing them credible information, but they are rare in that context. In an experiment with 3,182 patients at 128 tuberculosis (TB) treatment centers in India, we find peers are indeed more effective than health workers in bringing in new suspects for testing, and low-cost incentives of about US 3 per referral considerably increase the probability that current patients make referrals that result in the testing of new symptomatics and the identification of new TB cases. Peer outreach identifies new TB cases at 25%-35% of the cost of outreach by health workers and can be a valuable tool in combating infectious disease.
Keywords: O1; I1; 330; tuberculosis; referrals; social networks; case finding; incentives; India; health